High glucose load and endotoxemia among overweight and obese Arab women with and without diabetes: An observational study. Issue 46 (13th November 2020) - Al-Disi, Dara; Ansari, Mohammed Ghouse Ahmed; Sabico, Shaun; Wani, Kaiser; Hussain, Syed Danish; Elshafie, Mona M.; McTernan, Philip; Al-Daghri, Nasser M.
Abstract : Abstract: Dietary intake influences gut microbiota activity. Nevertheless, there is a lack of evidence available that illustrates the acute effects of high glucose meal on metabolic endotoxemia. The present study assessed the acute impact of high glucose meal on endotoxemia and other clinical parameters in Saudi females with varying degrees of glycemia. The subjects were 64 consenting pre-menopausal women, grouped into 3: control [n = 14 lean, non-T2DM, BMI = 22.2 ± 2.2 kg/m 2 ]; overweight [n = 16, non-T2DM, BMI = 28.5 ± 1.5 kg/m 2 ] and T2DM [n = 34, BMI = 35.2 ± 7.7 kg/m 2 ]. After an overnight fast, all subjects were given a standardized high-glucose (75 g) meal. Anthropometrics were taken and blood samples were withdrawn at baseline and postprandial (0, 2 and 4-hours), serum glucose, endotoxin and lipid profile were quantified. At baseline, total cholesterol, LDL-cholesterol, triglycerides and serum glucose levels were significantly higher ( P values <.01) whereas significantly lower HDL-cholesterol levels ( P  < .01) were observed in T2DM subjects compared to other groups. Baseline endotoxin levels were highest in the overweight group (3.2 ± 1.1 mmol/L) as compared to control (2.0 ± 0.5 mmol/L) and T2DM (2.7 ± 1.2 mmol/L) ( P  = .046). HDL-cholesterol, LDL-cholesterol and triglycerides, significantly decreased in the T2DM group after 2 hours ( P values <.05), whereas unremarkable changes observed in other groups. Lastly, endotoxin levels significantly increased only in the overweight group (3.2 ± 1.1 vs 4.2 ± 1.4 mmol/L; P  < .05), 4 hours postprandial. High glucose meal elevates endotoxemia only among overweight subjects and impairs dysbiosis.